Environmental Risk And Foreign Direct Investment: The Role Of Financial Sector Development And Tax Policies - Yiadom, E.B. (University Of Ghana, 2022)
Responding to climate change is at the forefront of policy and research at this crucial moment of the earth’s history. A two-pronged approach has emerged: mitigation and adaptation. This study relates to both the climate mitigation and adaptation strategies to resolving climate change. Specifically, the thesis contributes to the literature by (i) examining the moderating role of financial sector development on the effect of foreign direct investment (FDI) on environmental risk, (ii) decomposing financial sector development into its subcomponents: access, depth and efficiency, and examining the extent to which they aid or prevent foreign direct investment from harming the environment, (iii) exploring whether countries with ‘weak’ or better still low tax rate attract ‘dirty’ FDI to deteriorate their environment, (iv) investigating the impact of carbon tax adoption on foreign direct investment. The study employs standard approaches namely the generalized method of moments (GMM), dynamic panel threshold models, fixed effects, random effects, sample splitting, and partial effects computations to examine the linkages. The results from the various estimation strategies show that, the unmitigated effect of FDI on environmental risk is detrimental. However, FDI conditioned on the local financial sector development minimizes environmental risk. This means that countries that have a well-developed financial sector is able to channel FDI into green projects that improve the quality of the environment. Further, the dynamic panel threshold model reveals that financial development increases environmental risk at low regimes of the threshold but high regimes of financial development have the ability to reduce it. This means that the level of financial sector development matters in accounting for its impact on environmental risk. Therefore, assuming a linear relationship between the two variables could be problematic. This brings clarity to the literature on why some studies report positive effect of financial development on environmental risk and others show negative effect. We further decomposed financial development into its subcomponents to help examine their behaviours and recommend specific policy directions. The findings reveal that financial deepening and efficiency reduce environmental risk and can overturn the negative impact of FDI on the environment. However, financial access worsens environmental risk especially at lower levels and cannot make the FDI – environment nexus any better. But then again, high levels of financial access has the ability to reduce environmental risk. Also, after splitting the dataset into high and low financially developed economies, we report that FDI is more environmentally depressive among low financially developed economies. Third, on the effect of tax policies on the FDI-environmental risk nexus, the study finds support that the tax channel is the main medium through which FDI worsens environmental risk. By discomposing tax policy into low and high regimes, the study reports that countries that deliberately reform tax policy to bait FDI have higher environmental risk. Therefore, using tax policy to lure FDI amount to short-changing capital risk for environmental risk. Finally, We set up the Dynamic Stochastic General Equilibrium (DSGE) model to estimate the effect of carbon tax adoption on FDI. The findings from this exercise show that the direct effect of the carbon tax on FDI is repressive. However, if the revenue from the carbon tax is recycled into the economy, the carbon tax will have a significant positive effect on FDI. Hence, the study corroborates the double dividend theory. The findings further suggest that a carbon tax of around US$8.5/ton is reasonable to enhance inward FDI but a carbon tax either above US$25/ton or below US$3/ton will be detrimental to the African region. Also, the entrenched negative relationship between FDI and taxes is worsened if the additional carbon tax is levied among high tax regime countries than their counterparts. The findings of this thesis churn out several contributions to knowledge and literature. The African context in the environmental economics and carbon tax policies are marginalized in the existing literature. This study opens up the frontiers to the discussions on the implications of carbon tax introduction on the free movement of international capital. As a forerunner on the subject of carbon tax’s effect on FDI in both Africa and the globe, this study offers reasons why many countries have not implemented a carbon tax despite the numerous benefits associated with it. This study also leads the way in advancing that the finance and the tax channels are the yet-to-be explored factors that account for the impact of FDI on the environment. The existing literature associates the negative effect of FDI on the environment with institutional quality. However, institutional quality is broad and encompasses almost everything in the administration of a country. This leaves policymakers helpless as the specific aspect of institutions that can mitigate the harmful environmental effects of FDI. This thesis brings finality to this policy debacle and recommends that retooling tax policies and enhancing financial deepening and efficiency could improve the effect of FDI on the environment. Keywords: environmental risk, foreign direct investment, financial sector development, carbon tax, tax policies, and generalized method of moment.
PhD. Finance
Keywords: Tax Policies; Foreign Direct Investment; Financial Sector Development